A randomised, double‐blind, placebo‐controlled trial of nightly sildenafil citrate to preserve erectile function after radiation treatment for prostate cancer. Issue 1 (18th October 2012) - Ilic, Dragan; Hindson, Ben; Duchesne, Gillian; Millar, Jeremy L
Abstract Introduction Erectile dysfunction (ED) is a common adverse event associated with treatment for prostate cancer. This study aimed to identify whether early, regular use of sildenafil after radiation treatment for prostate cancer is effective at reducing the rate of ED at 2 years. Methods A randomised controlled trial with 27 men planned for radiation treatment for localised prostate cancer recruited from a single radiotherapy centre in Australia. Men were randomised to receive daily sildenafil, or a placebo tablet, for 6 months. The primary end‐point was erectile function, as measured by the International Index of Erectile Function (IIEF) score, at 2‐year follow‐up. The abridged IIEF‐5 survey was also used during the treatment period, and could be derived from the full IIEF at other time‐points. Two‐sided Student's t‐tests and Mann–Whitney U‐tests were used for the analysis of continuous outcomes, with Fisher's exact test for dichotomous outcomes. Results No difference was seen at 2 years in the primary end‐point, and IIEF scores did not differ significantly between groups during the study. Men in the sildenafil group exhibited significantly better IIEF‐5 scores at 4 weeks (P = 0.02) and 6 months (P = 0.02). There was no difference in erectile function scores between the two groups throughout the treatment period. No significant difference in adverse events was identified between the two groups. Conclusion There was no evidence from this trial that sildenafil provides long‐term erectile function for patients while on medication. Regular use of sildenafil may improve short‐term sexual function for patients while on medication. Larger trials are required to examine the effectiveness of implementing sildenafil for prostate cancer patients undergoing radiation treatment.